Exploring the Symbiodinium rare biosphere provides evidence for symbiont switching in reef-building corals - Boulotte, Nadine M (ISME J, 2016)
Reef-building corals possess a range of acclimatisation and adaptation mechanisms to respond to seawater temperature increases. In some corals, thermal tolerance increases through community composition changes of their dinoflagellate endosymbionts (Symbiodinium spp.), but this mechanism is believed to be limited to the Symbiodinium types already present in the coral tissue acquired during early life stages. Compelling evidence for symbiont switching, that is, the acquisition of novel Symbiodinium types from the environment, by adult coral colonies, is currently lacking. Using deep sequencing analysis of Symbiodinium rDNA internal transcribed spacer 2 (ITS2) PCR amplicons from two pocilloporid coral species, we show evidence consistent with de novo acquisition of Symbiodinium types from the environment by adult corals following two consecutive bleaching events. Most of these newly detected symbionts remained in the rare biosphere (background types occurring below 1% relative abundance), but one novel type reached a relative abundance of ~33%. Two de novo acquired Symbiodinium types belong to the thermally resistant clade D, suggesting that this switching may have been driven by consecutive thermal bleaching events. Our results are particularly important given the maternal mode of Symbiodinium transmission in the study species, which generally results in high symbiont specificity. These findings will cause a paradigm shift in our understanding of coral-Symbiodinium symbiosis flexibility and mechanisms of environmental acclimatisation in corals.